Pengalaman Hidup Penderita Filariasis - Ariyanto, Ariyanto (Jurnal Akademika Baiturrahim Jambi, 2025)
Filariasis is a general term used for Lymphatic Filariasis (Filariasis), a parasitic disease caused by an infection of filarial worms. It is often referred to as 'elephantiasis' due to the swelling and thickening of the skin, which resembles an elephant's leg. This study aims to explore the lived experiences of filariasis sufferers. The research employs a qualitative descriptive method with a phenomenological approach. There are five participants in this study. Data analysis in this research uses the Collaizi approach. The results of the study reveal that, first, the initial experience of suffering from filariasis is shock, confusion, and feelings of uncertainty. Second, the experiences of filariasis sufferers while experiencing clinical symptoms include fever, pain, swelling, limitations in activities, and fatigue. Third, the emotional and psychological disturbances experienced by filariasis sufferers are feelings of shame, annoyance, and resignation. Fourth, the existence of socioeconomic burdens includes withdrawing from social interactions and economic difficulties. Fifth, the experiences of filariasis patients in accessing healthcare services are a persistent illness despite several treatments, unsatisfactory healthcare services, and hopes for better health. The research results expect that better healthcare services will include easier and more affordable access to treatment, as well as a holistic approach to treatment that not only focuses on physical aspects but also psychosocial aspects, enhancing promotive, preventive, curative, and rehabilitative efforts.